Anomalous superconducting phase diagram in UBe13. (18th March 2015) - Matsuno, H; Morita, K; Kotegawa, H; Tou, H; Haga, Y; Yamamoto, E; Onuki, Y
Abstract: Surface impedance measurements Zs, where Zs consists of surface resistance Rs and surface reactance Xs, were carried out for a single crystal UBe13 . Rs exhibits unusual field dependence with a significant hump around the H *, which is nearly equal to 0.6 H c 2 . This behavior indicates that the strong vortex pinning occurs around H * .